THE CORRELATION BETWEEN A SUPERVISION COMPETENCE AND A CONFLICT MANAGEMENT STYLE OF HEAD OF NURSING DEPARTMENT IN GOVERNMENT HOSPITAL IN BANDA ACEH - Halimatussakdiah Halimatussakdiah; Ampera Miko; Isneini Isneini (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Most of head of nursing department even nurses in hospital uses compromising conflict management style  about 13 %. While collaborating and avoiding style are only used at least 5,6 %. The difference in applying conflict management style is influenced by some individual factors including knowledge, skill and the ability in supervision competence. The purpose of this research is to find out the correlationbetween supervision competence and conflict management style ofhead of nursing department in goverment hospital in Banda Aceh. Quantitative method with cross sectional design was used in this research. This research was conducted in RSUD dr. Zainal Abidin and in BLUD – RSJ (mental illness service unit) Banda Aceh toward 77 heads of nursing department who perfoming supervision (total sampling). The method used in collecting data is questionary distribution. Chi-square technique is used to analyse the corellation between supervision competence and conflict management style of  head of nursing department. The result of this research shows that 84,4% of head of nursing department is incompetent in applying conflict management style and 92,2% of those generally used intergration style in problem solving. The result of statistict test shows that there is no significant corellation between supervision competence of head of nursing department and dominating, integrating, compromising, avoiding style and there is no obligation to apply conflict management style by head of nursing departement in conducting supervision  at hospital in Banda Aceh. The lower number of competent supervisor and the higher number of inappropriate style applying by supervisor in manage conflict can decrease the quality of controlling in hospitals. It is strongly sugessted that nurse supervisors improve supervision competence and  knowledge related to conflict management style through training, workshop, seminar and continual education.Keywords : head of nursing department, supervision competence , conflict management style